Vitamin B12 and Progression of White Matter Lesions. A 2-Year Follow-Up Study in First-Ever Lacunar Stroke Patients - van Overbeek, Ellen C. (Public Library of Science, 2013)
In cross-sectional studies periventricular white matter lesions (WML) were related to low plasma levels of vitamin B12. Whether low vitamin B12 levels are also related to progression of WML is still unknown. We studied baseline vitamin B12 levels and its association with progression of WML over 2 years of follow-up in first-ever lacunar stroke patients. In 107 first-ever lacunar stroke patients in whom baseline brain MRI and vitamin B12 status were available, we obtained a follow-up brain MRI after 2 years. We assessed progression of periventricular WML (pWML) and deep WML (dWML) using a visual WML change scale. We studied the relationship between baseline levels of plasma vitamin B12 and progression of WML after 2 years of follow-up by binary logistic regression analyses. Vitamin B12 deficiency was more frequent in patients with progression of pWML compared to those without progression (41.9% and 19.7% respectively, p = 0.02). Corrected for sex and age, progression of pWML was associated with lower baseline levels of vitamin B12 (OR 1.42 per 50 unit decrease, 95% CI 1.00-1.92). Vitamin B12 levels were not associated with progression of dWML. In conclusion progression of pWML after 2 years of follow-up relates to low levels of vitamin B12 at baseline in first-ever lacunar stroke patients. Whether this population could benefit from vitamin B12 supplementation is unknown and requires further investigation.